Broad Ligament Pregnancy: A Rare Case Repor - Siddiqui, Maruf; Ghafoor, Nusrat; Naznine, Fahmida; Abdullah, Rusmila Shamim; Chowdhury, T A (Journal of Dhaka Medical College, 2020)
Broad ligament pregnancy is a rare obstetric condition. Its diagnosis is quite difficult and management is challenging. Here we report a case of a 26 years old primi gravida conceived following laparoscopy and ovulation induction. Diagnosis of the broad ligament pregnancy was done by a transvaginal ultrasound at her 9 weeks and was proceded with laparoscopy followed by laparotomy. A right broad ligament pregnancy was found and the sac with fetus was removed. Laparoscopy was converted into a laparotomy as there was an uncontrollable bleeding from the broad ligament. Here we present a case of this extreme rare type of broad ligament pregnancy. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 123-125